PENGARUH PELAKSANAAN GOOD GOVERNMENT GOVERNANCE TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) PEMERINTAH KABUPATEN GRESIK (Fakultas Ekonomi Universitas Gresik, 2016)
The research aims to examines and proves the influence of public accountability, transparency public policy, participation, and rule of law to the performance Satuan Kerja Perangkat Daerah (SKPD) District Government Gresik. This research is important especially in financial performance SKPD is still a lot of extravagance and inefficiency that is very important in materialized of implementation good government governance. This research uses quantitative approach with multiple linear regression. Amount of sample taken 31 respondents and data collection is done with a questionnaire to obtain data. Result of this research is that public accountability have positive significant influence to the performance SKPD District Government Gresik, transparency public policy have negative influence to the performance SKPD District Government Gresik, the participation have positive significant influence to the performance SKPD District Government Gresik, and rule of law have positive significant influence to the performance SKPD District Government Gresik.